Naturalistic generative narratives reveal effects of social characteristics on decision-making - Wong, Ethan; Williams, Ofir; Williams, Ziv M.; Báez-Mendoza, Raymundo (Frontiers in Psychology, 2024)
The social characteristics of others can powerfully influence our decisions. They can also be broadly impacted by the social context in which these choices are made, making the effects of these characteristics on decision-making especially challenging to understand. Here, we developed a Generative Narrative Survey that provided participants with naturalistic scenarios that richly varied in social context and theme but that also systematically varied the characteristics of the social agents involved, followed by a question. An example of this narrative is "You're a tourist, and you're trying to take a picture of yourself with your phone. A black male comes up to you and offers to take the photo for you. Do you hand them your phone?" After validating this approach using feeling thermometer measures, we found that the emotional states of others had the strongest and most consistent effect on the participants' choices. More notably, whereas most characteristics had independent effects on decision-making, social features such as the inferred socioeconomic status of others significantly influenced the effect that race had on the participant's judgments. Moreover, the social context of the agent's interactions with other agents had a significant additive effect, especially when the emotional states of the agents in the scenarios contrasted. The influence of these characteristics on the participants' choices was also markedly affected by their demographics, especially when contrasting with that of the agents involved, and were often driven by the participants' reported political views. Together, these findings reveal how the mixture of social characteristics, context, and personal views influence decision-making and highlight the use of naturalistic generative narrative surveys in studying human behavior.